A Total Organic Aqueous Redox Flow Battery Employing a Low Cost and Sustainable Methyl Viologen Anolyte and 4‐HO‐TEMPO Catholyte. Issue 3 (1st December 2015) - Liu, Tianbiao; Wei, Xiaoliang; Nie, Zimin; Sprenkle, Vincent; Wang, Wei
Abstract : Increasing worldwide energy demands and rising CO2 emissions have motivated a search for new technologies to take advantage of renewables such as solar and wind energies. Redox flow batteries (RFBs) with their high power density, high energy efficiency, scalability (up to MW and MWh), and safety features are one suitable option for integrating such energy sources and overcoming their intermittency. However, resource limitation and high system costs of current RFB technologies impede wide implementation. Here, a total organic aqueous redox flow battery (OARFB) is reported, using low‐cost and sustainable methyl viologen (MV, anolyte) and 4‐hydroxy‐2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl (4‐HO‐TEMPO, catholyte), and benign NaCl supporting electrolyte. The electrochemical properties of the organic redox active materials are studied using cyclic voltammetry and rotating disk electrode voltammetry. The MV/4‐HO‐TEMPO ARFB has an exceptionally high cell voltage, 1.25 V. Prototypes of the organic ARFB can be operated at high current densities ranging from 20 to 100 mA cm 2, and deliver stable capacity for 100 cycles with nearly 100% Coulombic efficiency. The MV/4‐HO‐TEMPO ARFB displays attractive technical merits and thus represents a major advance in ARFBs. Abstract : Low‐cost redox active materials are critical to achieving cost effective redox flow battery technology based, large‐scale energy storage. An organic aqueous redox flow battery is reported, using a low‐cost and sustainable methyl viologen (MV) and 4‐hydroxy‐2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl (4‐HO‐TEMPO) redox couple, and a benign NaCl supporting electrolyte. The MV/4‐HO‐TEMPO flow battery has a high cell voltage of 1.25 V with excellent cycling performance.